2019
DOI: 10.1016/j.socec.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Time pressure and honesty in a deception game

Abstract: Previous experiments have found mixed results on whether honesty is intuitive or requires deliberation. Here we add to this literature by building on prior work of Capraro (2017). We report a large study (N=1,389) manipulating time pressure vs time delay in a deception game. We find that, in this setting, people are more honest under time pressure, and that this result is not driven by confounds present in earlier work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 41 publications
4
53
1
2
Order By: Relevance
“…The case of honesty is particularly interesting. When players do not initially know the payoffmaximizing strategy, then System 1 promotes honesty (Foerster et al, 2013;Capraro, 2017;Capraro et al, 2019), and this is in line with the predictions of the GSHH. However, when players know the available actions and their consequences since before the cognitive process manipulation, then System 2 promotes honesty, especially when dishonesty harms an abstract other (Köbis et al, in press).…”
Section: Limitations Of the Gshh And Directions For Future Researchsupporting
confidence: 71%
See 2 more Smart Citations
“…The case of honesty is particularly interesting. When players do not initially know the payoffmaximizing strategy, then System 1 promotes honesty (Foerster et al, 2013;Capraro, 2017;Capraro et al, 2019), and this is in line with the predictions of the GSHH. However, when players know the available actions and their consequences since before the cognitive process manipulation, then System 2 promotes honesty, especially when dishonesty harms an abstract other (Köbis et al, in press).…”
Section: Limitations Of the Gshh And Directions For Future Researchsupporting
confidence: 71%
“…They found that participants who are asked to report the outcome immediately are more honest than those under time delay. Along the same lines, Capraro (2017) and Capraro, Schulz and Rand (2019) found that a 5-second time pressure increased honesty in a sender-receiver game (in which the private information was communicated at the same time as the timer started), compared to a 30-second time delay. Lohse, Simon and Konrad (2018) found that time pressure increased honesty in a situation in which participants could misreport a private information for their benefit, and the effect was due to a lack of awareness of the opportunity to lie.…”
Section: Review Of the Empirical Evidencementioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, we have also conducted a time pressure study (analyzed in the Appendix). This is a significant contribution in itself, because the role of time pressure and, more generally, the role of intuition on honesty has been at the center of the debate in the last years (Andersen et al, 2018;Cappelen et al, 2013;Capraro, 2017;Capraro et al, 2019;Debey et al, 2012;Gino et al, 2011;Gunia et al, 2012;Lohse et al, 2018;Mead et al, 2009;Shalvi et al, 2012;Spence et al, 2001;Van't Veer et al, 2014;Walczyk et al, 2003), as a part of the more general research program of classifying social behaviors according to whether they are intuitive or reflective Cococcioni, 2015, 2016;Capraro et al, 2017;Corgnet et al, 2015;Lotz, 2015;Rand et al, 2012Rand et al, , 2014Rand et al, , 2016Rand, 2016). In our case, time pressure has no effect on the overall rate of honesty.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, economists and psychologists have started studying (dis)honesty using incentivized economic problems (Erat and Gneezy, 2012;Fischbacher and Föllmi-Heusi, 2013;Gneezy, 2005;Hurkens and Kartik, 2009;Kartik, 2009;Schweitzer, 2014, 2015;Mazar et al, 2008;Sheremeta and Shields, 2013;Weisel and Shalvi, 2015;Wiltermuth, 2011). For example, they have explored the effect on honesty of many exogenous and endogenous variables, such as: demographic characteristics (Abeler et al, 2019;Biziou-van Pol et al, 2015;Cappelen et al, 2013;Capraro, 2018;Childs, 2012;Dreber and Johannesson, 2008;Friesen and Gangadharan, 2012;Erat and Gneezy, 2012); social and moral preferences (Biziou-van Pol et al, 2015;Schweitzer, 2014, 2015;Shalvi and De Dreu, 2014); incentives (Dreber and Johannesson, 2008;Erat and Gneezy, 2012;Ezquerra et al, 2018;Fischbacher and Föllmi-Heusi, 2013;Gneezy, 2005;Gneezy et al, 2018;Kajackaite and Gneezy, 2017;Mazar et al, 2008); and cognitive mode (Andersen et al, 2018;Cappelen et al, 2013;Capraro, 2017;Capraro et al, 2019;Gino et al, 2011;Gunia et al, 2012;Lohse et al, 2018;Shalvi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%